PELATIHANPEMBUATANDANPENGEMASANNATA DECOCO - Sarastri Mumpuni (Asian Journal of Innovation and Entrepreneurship, 2013)
Coconut (Cocos nucifera) is the sole member of the clan of the tribe palmCocos-arenan or Arecaceae. This plant is used almost all parts by humans that isconsidered as a versatile plant, especially for coastal communities. This tamanan rangingfrom leaf tip to tip helpful rootof all. Especially coconut very nutritious for health. Withhard skin and white flesh, coconuts can be used to treat poisoning. Consumption of fruitand coconut water when accidentally consumed or expired spoiled food can neutralizetoxins. Even ordinary coconut water given to those who either accidentally or drinkpoison insects, as first aid. The training program manufacture and packaging of nata decoco that the authors want is training about how making nata de coco, this is donebecause the coconut as the abundant natural resources not fully utilized becomeanother flagship product. The purpose of the program-making and packaging nata decoco is to provide knowledge that there is alternative processing of coconut. Besidesproviding the motivation to make the domestic industry. The training programmanufacture and packaging of nata de coco is done in three phases counseling aboutmaking nata de coco, information about the packaging and the practice of making nata decoco. The program is performing well, the trainees can learn how making nata de cocoin an easy way. In addition, participants can devote opinion of how to package theresults nata de coco to be marketed.